Candida auris infection; diagnosis, and resistance mechanism using high-throughput sequencing technology: a case report and literature review - Hong, He; Ximing, Yang; Jinghan, Ma; Al-danakh, Abdullah; Shujuan, Pan; Ying, Lin; Yuting, Yang; Yuehong, Liu; Xingwei, Yao (Frontiers in Cellular and Infection Microbiology, 2023)
Candida auris (C. auris), a recently developing fungal disease with high virulence, easy transmission, and substantial medication resistance in hospitals, poses a growing danger to human health. 2009 saw the first description of the disease in the ear canal of an older Japanese patient. Since its initial isolation, the presence of C. auris across six continents has been a cause for severe concern among medical professionals and scientists. According to recent findings, C. auris is connected with five geographically different lineages and significant rates of antifungal resistance. Furthermore, C. auris infections in healthcare settings lack appropriate treatment options and standardized strategies for prevention and control. This results in many treatment failures and hinders the elimination of C. auris in healthcare institutions. To examine the drug resistance mechanism of C. auris and to aid in clinical therapy, we provide a case of C. auris infection along with a short review of the relevant literature.An 81-year-old female with cerebral hemorrhage was admitted to the hospital and diagnosed with a urinary catheter-related C. auris. The sample was evaluated and reported in terms of culture, identification, drug sensitivity, and gene sequencing. We also evaluated the relationship between the morphology of the isolated strains and their drug resistance. Whole-genome sequencing yielded the genes ERG11-Y132F, CDR1-E709D, TAC1B-Q503E, and TAC1B-A583S; however, no additional loci included alterations of concern, according to our results. ERG11-Y132F and TAC1B-A583S are drug-resistant gene loci, whereas CDR1-E709D and TAC1B-Q503E are unidentified variants.We discover a C. auris case of specific a strain in an old female that has some drugresistant genes, and some genes may be different from already reported gene sites . Gene locus, mutation, and drug resistance mechanism studies may contribute to the creation of innovative drugs and therapeutic treatments. Clinicians and microbiologists must be aware of this globally spreading yeast, which poses substantial hospital diagnostic, treatment, and infection control challenges. Future multicenter research must be performed to uncover this health threat and provide new, effective treatments.